Sororidade com saber goiano: O feminismo pioneiro de Consuelo Nasser - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
The work discusses the trajectory of Consuelo Nasser and analyzes why her legacy is silenced. She was one of the pioneers of feminism in the State of Goiás, a journalist and lawyer and founder of the “Centro de Valorização da Mulher” (Cevam), an initiative in relation to problems arising from violence against women. Active journalist, edited the weekly “O Cinco de Março” (1959-1979), was responsible for the financial management of the newspapers “Diário da Manhã” (1982-1984) and “Folha de Goyaz” (1984), founded and edited the newspaper “Edição Extra” (1984-1985) ) and the “Revista Presença” (1986-1991). After a trajectory of great achievements, apparently due to the death of her son, Fábio Nasser, Consuelo shot herself on August 20, 2002. Throughout the project, her biography was narrated and analyzed, and was investigated. why her work is not yet recognized. Through his legacy, Consuelo is a reference of resistance to the abuses suffered by women. Despite her family's attempts to eternalize her name, she is not favored by the collective nor by most feminists. Despite the discretion of her memory, Consuelo Nasser stands out for her legacy of fighting for women's rights.
Sorority with knowing goiano: Consuelo Nasser's pioneering feminism
Keywords: Feminismo - História - Goiás(Estado); Feminismo - Consuelo Nasser - Goiás(Estado); Mulheres - Discriminação e violência - Goiás(Estado); Feminism - History - Goiás (State); Feminism - Consuelo Nasser - Goiás (State); Women - Discrimination and violence - Goiás (State); CIENCIAS HUMANAS::SOCIOLOGIA